Evaluation of modulus of elasticity based on vibration modes identification using acoustic methods. (2022) - Prezelj, Jurij; Emri, Igor; Nikonov, Anatolij
Abstract: Paper presents an experimental methodology that allows the reconstruction of the modulus of elasticity of thin elastic plates based on vibration mode analysis using a simple microphone to locate nodes by exploiting the properties of an acoustic Very Near Field (VNF). The shape of the plate used in measurements was determined from analytical and FEM simulations of plate vibration under harmonic excitation. The measurements were carried out on a 4 mm thick aluminum plate with the dimensions 200 mm × 900 mm suspended with two elastic strings to achieve FFFF boundary condition. The results showed that the proposed methodology allows accurate prediction of modulus of elasticity for thin plates. In addition, it was found that reliable measurements can be performed at background noise levels (measured in 1/3 octave band) up to 40 dB.